A sportomics soccer investigation unveils an exercise-induced shift in tyrosine metabolism leading to hawkinsinuria - França, Thássia Casado Lima; Muniz-Santos, Renan; Caetano, Luiz Carlos; Souza, Gustavo H. M. F.; Goulart, Henrique Fonseca; Assis, Marcio; Bottino, Altamiro; Bassini, Adriana; Santana, Antonio Euzébio Goulart; Prado, Eduardo Seixas; Cameron, L. C. (Frontiers in Nutrition, 2023)
Tyrosine metabolism has an intense role in the synthesis of neurotransmitters. Our study used an untargeted, sportomics-based analysis of urine samples to investigate changes in metabolism during a soccer match in 30 male junior professional soccer players. Samples were collected before and after the match and analyzed using liquid chromatography and mass spectrometry. Results showed significant changes in tyrosine metabolism. Exercise caused a downregulation of the homogentisate metabolites 4-maleylacetoacetate and succinylacetone to (p = 4.69E-5) and 16% (p = 4.25E-14), respectively. 4-Hydroxyphenylpyruvate, a homogentisate precursor, was found to be upregulated by 26% (p = 7.20E-3). The concentration of hawkinsin and its metabolite 4-hydroxycyclohexyl acetate increased ~6-fold (p = 1.49E-6 and p = 9.81E-6, respectively). Different DOPA metabolism pathways were also affected by exercise. DOPA and dopaquinone increased four- to six-fold (p = 5.62E-14 and p = 4.98E-13, respectively). 3-Methoxytyrosine, indole-5,6-quinone, and melanin were downregulated from 1 to 25%, as were dopamine and tyramine (decreasing to up to 5% or 80%; p = 5.62E-14 and p = 2.47E-2, respectively). Blood TCO2 decreased as well as urinary glutathione and glutamate (40% and 10% respectively) associated with a two-fold increase in pyroglutamate. Our study found unexpected similarities between exercise-induced changes in metabolism and the inherited disorder Hawkinsinuria, suggesting a possible transient condition called exercise-induced hawkinsinuria (EIH). Additionally, our research suggests changes in DOPA pathways may be involved. Our findings indicate that soccer exercise could be used as a model for understanding Hawkinsinuria and maybe other tyrosine metabolism disorders.